Nghiên cứu hiệu ứng gia cường của cacbon nano tube đối với vật liệu polyme tổ hợp trên cơ sở cao su thiên nhiên/styren butadien và cao su thiên nhiên/polypropylen - Quang và cộng sự, Nguyễn (Vietnam Journal of Chemistry, 2014)
In this work, the influences of multi-walled carbon nanotubes (MWCNTs) on mechanical properties and structure of polymer blends natural rubber/polypropylene (NR/PP=50/50) and natural rubber/styrene butadiene rubber (NR/SBR = 50/50) were characterized. There was a maximal reinforcement effect at ratio of 1% wt. MWCNTs for both polymer blends determined. The thermo mechanical analysis (TMA) and the stress cycle measurements of samples after accelerated climate test showed that polymer composite basing on NR/SBR/MWCNT was more stable than NR/PP/MWCNT. Transmission electron microscope examinations proved that MWCNTs well distributed and well adhered to polymer blends